Feasibility Study for Catfish Farming Business in A Bucket in Kp Biru, Malang, East Java, Indonesia - Susilawati, Lena; Karnita, Lilis (Economic: Journal Economic and Business, 2022)
The Covid-19 pandemic that occurred in Indonesia has had a negative impact on various sectors such as health, economy, and others. There needs to be a strategic solution to survive. There are various ways people survive and win against the Covid-19 pandemic. The community's economy is destroyed. This is certainly a trigger for people to do anything to survive. The emergence of household-scale businesses. Creative ideas are emerging. One of them is damber catfish cultivation in kp Biru, Malang, East Java. The author is interested in making this damber catfish cultivation object. business feasibility study research. Catfish is one type of fish that can live in high density. This fish has a good conversion rate of feed into body weight. With these properties, catfish farming will be very profitable if done intensively. Catfish (Clarias sp) is one type of freshwater fish consumption. Catfish is a type of catfish or in other words a fish that has a mustache. Catfish are raft and caninal. The characteristics of catfish are elongated and slightly rounded body shape, on the pectoral fins there are hard and sharp spines (patil), striped body color with a flat head and there is a mustache and slippery because it does not have scales. This fish has an additional breathing apparatus in the form of a modification of its gill arc, namely arborescent. This catfish has a fairly complete nutritional content. The chemical and nutritional content of catfish are fat, protein, vitamins (BI, B). The study used descriptive qualitative methods and participatory methods, observations and interviews. The study also used SWOT analysis to map strengths, opportunities, weaknesses and threats. The SWOT method can be used to determine strategies, fix deficiencies and can also read competitors. The final result of this damber catfish business feasibility study can be an indicator of how to run this business better from the management aspect including product, management, HR, marketing and financial aspects. Good business management will increasingly provide promising benefits. The purpose of this research is to encourage people to be more active, creative and productive and to continue to innovate to create something different. The harvest can be developed for processed products so that they become added value and become various kinds of processed innovations. With the innovation of this catfish processed product, it is hoped that it can change the community's economy to be stronger. Be more independent and Isa will create a new strong businessman